P1163IMPACTS OF IRON-BASED PHOSPHATE BINDER ON ANEMIA AND IRON METABOLISM IN PERITONEAL DIALYSIS PATIENTS: A CROSS-SECTIONAL, LONGITUDINAL MULTICENTER STUDY IN KANAGAWA, JAPAN. (6th June 2020) - KOIBUCHI, KIYOTO; Amagasa, Masahito; Otsuka, Tomoyuki; Koitabashi, Kenichiro; Kawarazaki, Hiroo; Komukai, Daisuke; Murasawa, Masaru; Taki, Yasuhiro; Aoyama, Togo; Nishiwaki, Hiroki; Sakurada, Tsutomu
Abstract: Background and Aims: Iron-based phosphate binder (IPB) is a noncalcium phosphate binder that demonstrated sustained serum phosphorus control, good tolerability and lower pill burden compared with sevelamer carbonate in a Phase 3 study conducted in dialysis patients. These efficacy of IPB has been demonstrated for hemodialysis (HD) patients, but few studies have focused on patients undergoing peritoneal dialysis (PD). We evaluated efficacy of IPB and focused on effects for anemia and iron metabolism in patients on PD. Method: This study was a cross-sectional, longitudinal multicenter study conducted by PD OASIS, organized committee in Kanagawa Japan. We analyzed the effects of IPB during a 6 months observation period in chronic kidney disease patients on PD who had administrated IPB, Ferric citrate hydrate and Sucroferric oxyhydroxide, between 2017 and 2019. The primary endpoint was the changes of phosphate, and several secondary endpoints were assessed: calcium, intact PTH, RBC, hemoglobin, MCH, RDW-VC, Fe, TSAT, Ferritin, albumin, CRP, monthly dosage of Erythropoietin stimulating agents (ESA) and ESA resistance index (ERI). In addition, we assessed the association between these markers and iron metabolism utilizing multivariate logistic regression analysis. Results: A total of 102 patients were registered in the study who had received IPB. The initial doses of Ferric citrate hydrate and Sucroferric oxyhydroxide were 1010.9 ±400.9 mg and 941.7 ±502.9 mg daily, finally increased to 1213.6 ±559.9 mg and 1310.0 ±521.8 mg respectively at the end of the observation. We observed a significant reduction of serum phosphate to 5.27 ± 0.98 mg/dL from 6.56 ± 1.52 mg/dL with follow-up of six months (p < 0.01). At the end of the study, 76.4% of participants had achieved the target of less than 6 mg/dL. The hemoglobin, TSAT and Ferritin increased significantly from 10.47 ±1.26 g/dl, 27.95 ±11.05 % and 139.0 ±147.6 ng/mL to 11.17 ±1.16 g/dl, 40.46 ±15.00 % and 305.9 ±232.0 ng/mL respectively in six months (p < 0.01). No significant changes of serum calcium, intact parathyroid hormone (PTH) and CRP occurred over the study period. The monthly dosage of ESA was significantly decreased after administration with IPB and ERI significantly improved to 0.11±0.12 (μg/month/kg/g Hb) from 0.21±0.16 (μg/month/kg/g Hb) (p<0.01). Hemoglobin overshoot, an increase of more than 12 g/dl, was observed in 27.5% patients. This related low MCH and high RDW-VC at baseline which was proven by multivariate logistic regression. Additionally, we assessed the factors of ferritin increase because it was remarkable in follow-up six months compared to HD patients. In multivariate analysis, phosphate (Odds ratio 5.85, 95%CI 1.18-91.77, p=0.027), intact PTH (0.99, 0.97-1.15, p=0.015), hemoglobin (Odds ratio 0.10, 95%CI 0.05-0.59, p=0.025), RBC (Odds ratio 1.16, 95%CI 1.04-1.41, p=0.003), and RDW-CV (Odds ratio 0.44, 95%CI 0.10-0.99, p=0.046) were significantly associated with ferritin increase more than 300 ng/ml, after adjusted. Conclusion: This study confirmed the efficacy of Iron-based phosphate binder, Ferric citrate hydrate and Sucroferric oxyhydroxide, in the treatment of hyperphosphatemia in PD patients. In addition, IBP caused secondary effects of anemia improvement and ESA dosage reduction resulting in ERI improvement. However, in this study, the increase in ferritin levels was remarkable. It may be because PD does not lose iron by treatment compared to HD. Therefore, we should check iron metabolism more frequently for PD patients taking IPB than HD patients. It is necessary to further investigate the effects of IPB on anemia and iron metabolism in PD patients.